Challenges and Opportunities of Investment to the People of Sebeta Town, Oromia Regional State, Ethiopia - Bekelcha, Kebede Lemu (Journal of Social Economics Research, 2019)
This study deals with the challenges and opportunities of investment to the people of Sebeta town, Ethiopia. Currently, countries throughout the world are intensifying investment activities in African countries. Ethiopia is one of them. The focus of this study is to investigate the challenges and opportunities of investment to the people of Sebeta town of Oromia Regional State. To achieve this objective, both primary and secondary data was used. For this purpose, informants selected from the displaced people, government officials, workers of different investment types and selected residents of the town were participants of FGD, interview, observation and case study. In such away, 141 individuals were directly involved in this study. In anthropological studies, analysis is an instrument to extract meanings from the information obtained during the field work. In such a manner, data were presented in a qualitative type. The result of the study showed that local communities lost their land, rivers were contaminated by waste released from companies, labor exploitation and numbers of workers in several companies were disabled, and instability in the town. Investment also brought several opportunities for local people as source of income, skills and technology transfer. Local communities used daily labor, self-employment informal sector to sustain their livelihood. Based on the findings of the research, some alternatives were forwarded that could solve the problem and capitalize the opportunities available. Therefore, implementing proclamations and regulations of the country, prioritizing people in decision making and reconstructing the livelihoods of displaced households need emphasis by the concerned bodies.